Philippines : Technical Assistance Report-Monetary and Financial Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report focuses on Philippines's monetary and financial statistics (MFS). In order to align the coverage of the other depository corporations survey to statistical standards, the mission recommended the inclusion of the money market unit investment trust funds in the survey. With the compilation of other financial corporation's data, the Philippines is now able to produce intersectoral balance sheet approach (BSA). MFS with full coverage, together with quarterly international investment position and public debt statistics, are the building blocks for the BSA. The mission recommended a detailed action plan with the following priority recommendations carrying weight to make headway in improving MFS quality and completeness. The experience by BSP compilers on data reporting by Securities and Exchange Commission supervised corporations pointed to a need to enhance the Bangko Sentral ng Pilipinas's (BSP) authority to collect data for statistical purposes, which has been addressed by BSP management. Details on the priority recommendations and the related actions/milestones can be found in the action plan under Detailed Technical Assessment and Recommendations.